Synthesis and spectral investigation of colorimetric receptors for the dual detection of copper and acetate ions: application in molecular logic gates. Issue 8 (3rd August 2017) - Pangannaya, Srikala; Kaur, Arshiya; Mohan, Makesh; Raval, Keyur; Chand, Dillip Kumar; Trivedi, Darshak R.
Abstract: Colorimetric receptorsL1, L2 andL3 possessing –OH functionality as binding site and –NO2 as signalling unit with varied positional substitution of –OMe functionality has been designed and synthesised by simple Schiff base condensation reaction. ReceptorsL1, L2 andL3 showed selective response towards AcO −  ion among other interfering monovalent anions viz., F −, Cl −, Br −, I −, NO3 −, and .L2 imparts high selectivity towards AcO − ion assisted by push-pull effect of –NO2 and –OMe functionality in conjugation with imine linkage. The binding constant for L2–OAc complex was found to be 9.04 × 10 4  M −2 . L2 exhibited a detection limit of 0.61 ppm towards NaOAc. The selectivity ofL1 towards Cu 2+ ions with a lower detection limit of 1.81 ppm implies the role of electron donating –OMe in favouring the coordinative interaction of hetero atoms ofL1 with Cu 2+ ions. The selective detection of AcO − and Cu 2+ ions is further established with OR and INHIBIT logic gate application of receptorsL1, L2 andL3 correspondingly. The colorimetric studies reveal the role of OMe functionality in the selective detection of AcO − and Cu 2+ ions in aqueous media. Abstract :